ECG abnormalities in patients with subarachnoid haemorrhage and intracranial tumours. Issue 10 (October 1987) - Rudehill, A; Olsson, G L; Sundqvist, K; Gordon, E
Abstract : The incidence of and possible factors influencing ECG abnormalities were analysed in one patient group with subarachnoid haemorrhages (n = 406) and another with intracranial tumours (n = 400). The highest incidence of each ECG abnormality was always found in the patients with subarachnoid haemorrhages. In this group an ECG pattern, possibly attributable to the cerebral disease and comprising abnormalities of the T and U waves and prolongation of the Q-Tc interval, was frequently identified.